A comparative study of amplitude of low-frequence fluctuation of resting-state fMRI between the younger and older treatment-resistant depression in adults - Sun, Jifei; Guo, Chunlei; Ma, Yue; Du, Zhongming; Wang, Zhi; Luo, Yi; Chen, Limei; Gao, Deqiang; Li, Xiaojiao; Xu, Ke; Hong, Yang; Yu, Xue; et al. (Frontiers in Neuroscience, 2022)
Background: Treatment-resistant depression (TRD) may have different physiopathological neuromechanism in different age groups. This study used the amplitude of low frequency fluctuations (ALFF) to initially compare abnormalities in local functional brain activity in younger and older patients with TRD. Methods: A total of 40 TRD patients and 38 healthy controls (HCs) underwent resting-state functional MRI scans, and the images were analyzed using the ALFF method and further analyzed for correlation between abnormal brain regions and clinical symptoms in TRD patients of different age groups. Results: Compared with the older TRD, the younger TRD group had increased ALFF in the left middle frontal gyrus and decreased ALFF in the left caudate nucleus. Compared with the matched HC group, ALFF was elevated in the right middle temporal gyrus and left pallidum in the older TRD group, whereas no significant differences were found in the younger TRD group. In addition, ALFF values in the left middle frontal gyrus in the younger TRD group and in the right middle temporal gyrus in the older TRD were both positively correlated with the 17-item Hamilton Rating Scale for Depression score. Conclusion: Different physiopathological neuromechanisms may exist in patients with TRD at different ages, particularly in the left middle frontal gyrus and left caudate nucleus.ALFF abnormalities are more extensive in the older than in the younger depression patients.